Prospects for increasing efficiency of state social assistance to the population based on a social contract - A. S. Abroskin; N. A. Abroskina (Вестник университета, 2023)
The purpose of the study is to analyze the reasons for low efficiency of state social assistance based on a social contract and to prepare proposals for the program development and its inclusion in the state policy measures system to reduce the poverty level of the population of the Russian Federation. The program effectiveness problems have been studied in the chronology of its regulatory and methodological framework formation and development stages. By now the lack of significant results of the use of the social contract technology as a special type of state social assistance to low-income families in the research has been explained by the lack of a program’s theoretical model with target indicators defined at the basic stage and mechanisms for achieving them. As a possible solution to the problem of increasing the effectiveness of program, the prospects for its transformation into an activating type program have been examined. Various modifications of such programs are now widely used in international practice and recognized as effective tools in ensuring the growth and stabilization of income of poor people.